A systematic review on tobacco use among civilian populations affected by armed conflict. Issue 2 (13th March 2015) - Lo, Janice; Patel, Preeti; Roberts, Bayard
Abstract : Objective: To systematically examine evidence on tobacco use among conflict-affected civilian populations. Data sources: Primary quantitative and qualitative studies published in English up to April 2014. Bibliographic databases searched were EMBASE, Global Health, MEDLINE, PsycEXTRA, PsycINFO, Web of Science, Cochrane; with the main terms of: (Smoke*, tobacco*, cigarette*, nicotine, beedi, bidi, papirosi, dip, chew, snuff, snus, smokeless tobacco) AND (armed-conflict, conflict-affected, conflict, war, refugee, internally displaced, forcibly displaced, asylum, humanitarian). Grey literature was searched using humanitarian databases, websites and search engines. Study selection: Studies were independently selected by two reviewers, with a study outcome of tobacco use and a population of conflict-affected civilian populations such as internally displaced persons, refugees, residents in conflict-affected areas, residents and returning forcibly displaced populations returning in stabilised and postconflict periods. 2863 studies were initially identified. Data extraction: Data were independently extracted. The Quality Assessment Tool for Quantitative Studies and the Critical Appraisal Skills Programme for qualitative studies were used to assess study quality. Data synthesis: 39 studies met inclusion criteria and descriptive analysis was used. Findings were equivocal on the effect of conflict on tobacco use. Evidence was clearer on associations between post-traumatic stress and other mental disorders with nicotine dependence. However, there were too few studies for definitive conclusions. No study examined the effectiveness of tobacco-related interventions. The quantitative studies were moderate (N=13) or weak (N=22) quality, and qualitative studies were moderate (N=3) or strong (N=2). Conclusions: Some evidence indicates links between conflict and tobacco use but substantially more research is required.